O programa Acessa Escola e as influências da Indústria Cultural em tempos da cultura digital - Silva, Camila Perez da (Universidade Federal de São Carlos, 2017)
Public initiatives in the field of technological education in Brazil aim to minimize the problems related to digital exclusion through the mass distribution of computers to schools and the construction of collective internet access centers. Such initiatives, aimed at digital inclusion, are often advertised as synonymous with social inclusion policies. In order to problematize this reality, the present work investigated, in the light of the Critical Theory, the contradictions observed in the process of implementation of the program conceived by the State Department of Education of São Paulo called Acessa Escola, considered one of the most comprehensive policies of digital inclusion from the country. The analysis has shown that the numerous obstacles to ICT use in schools, such as low connectivity, the constant need for equipment maintenance and the lack of training courses for teachers, lead to the underutilization of the technological apparatus, contributing to disseminate the semiformation in the teaching units.
The Access to School program and the influences of the Cultural Industry in times of digital culture
Keywords: Indústria cultural; Inclusão digital; TIC; Acessa Escola; Cultural industry; Digital inclusion; ICT; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM